Sociodemographic factors associated with the delay in the diagnosis of tuberculosis in the regional teaching Hospital of Cajamarca from 2020 to 2024 - Rimarachín-Chávez, Ana María (2025)
Objetive: to evaluate the association between sociodemographic and clinical factors with delayed diagnosis and treatment of tuberculosis at the Cajamarca Regional Teaching Hospital from 2020 to 2024. Methods: A database comprising all tuberculosis cases from 2020 to 2024 was obtained from the Epidemiology Office of the Cajamarca Regional Teaching Hospital. Sociodemographic and clinical determinants associated with delays in tuberculosis diagnosis and treatment were analyzed. Out of a total of 275 patients, 64 cases were excluded due to incomplete records, leaving a final sample of 211 patients. Results: The final results of this study show a median diagnostic delay of 27 days. Of all the patients, 62% were male, and there was a similar distribution between pulmonary and extrapulmonary tuberculosis presentations. In the bivariate analysis between patient characteristics and diagnostic delay time, no statistically significant associations were found (p < 0.05); the same was observed for treatment delay time. Conclusion: The adult life-course stage showed a significant association with diagnostic delay. The remaining sociodemographic and clinical variables did not demonstrate a statistical association with delays in the diagnosis and treatment of tuberculosis at the Regional Teaching Hospital of Cajamarca. This finding may be attributable to the wide dispersion of the data and the particular characteristics of each region.